Challenging Neoliberal Paradigms: Non-State Organisations and Urban Community Gardens in Cape Town - Kanosvamhira, Tinashe P. (ACME, 2025)
The literature identifies a dual effect of urban community gardens, emphasising their potential to resist neoliberal urbanism while also acknowledging their inadvertent role in perpetuating it. This paper advances this discourse by analysing the paradoxical dynamics of urban community gardening in Cape Town, South Africa. It investigates the socio-political contexts and mechanisms that shape these dual dynamics, revealing how urban gardens simultaneously challenge and reinforce neoliberal governance. Drawing on qualitative methods, including document analysis, website reviews, and semi-structured interviews with non-state organisations in Cape Town, the study demonstrates how neoliberal environments cultivate gardens that uphold neoliberal values, often overlooking the structural drivers of food insecurity in disadvantaged areas. Crucially, this research identifies specific conditions such as the ideological orientation of civil society actors and their capacity to promote critical reflexivity and collective action that determine whether urban gardening initiatives resist or perpetuate neoliberal urbanism. The findings highlight the role of civil society organisations in raising awareness among urban gardeners and fostering participation in food justice initiatives that aim to empower marginalised communities and transform urban food systems. This paper underscores the importance of understanding the institutional contexts that mediate these interactions to advance equitable and sustainable food systems.